Video-assisted mediastinoscopy is safe in patients taking antiplatelet or anticoagulant therapy - Charlotte Cohen (Journal of Minimal Access Surgery, 2020)
Background: The aim of this study was to report our experience with video-assisted mediastinoscopy (VAM) in patients taking antiplatelet (AP) or anticoagulant therapies focusing on perioperative complications (especially haemorrhagic). Patients and Methods: We have done a retrospective study from a prospectively maintained database with diagnostic VAM (01/2008–06/2012). We included 54 patients with AP (41 patients – Group A) and anticoagulant (13 patients – Group B) therapies. The control group was formed by 263 patients (Group C). Data regarding the clinical records of the patients, operative time, per- and post-operative complications, total numbers of biopsies and the results of the pathologic examination were collected. We compared the groups A+B versus C, and then A versus C. Statistical differences were calculated by Chi-square test. Results: In Group A, we had two minor complications: cardiac arrhythmia and peroperative minor haemorrhage. The mean operative time was 29 min and the mean post-operative stay was 1.08 days. In Group B, we had one minor complication: Peroperative minor haemorrhage. The mean operative time was 35 min and the mean post-operative stay was 1.07 days. In Group C, the mean operative time was 28 min. One death occurred (mortality rate of 0.38%) because of cardiac arrest at the induction of anaesthesia. One major complication occurred (severe respiratory insufficiency needing re-intubation) and eight minor complications. Morbidity rate was 2.28%. Mean post-operative stay was 1.14 days. No statistical difference was noted between groups. Conclusion: VAM can be safely performed in patients receiving AP or anticoagulant treatments. There is no increase in peroperative bleeding or post-operative compressive cervico-mediastinal haematoma.